Relationship between nitrate headache and outcome in patients with acute stroke: results from the efficacy of nitric oxide in stroke (ENOS) trial. Issue 2 (5th November 2020) - Beishon, Lucy; Woodhouse, Lisa J; Bereczki, Daniel; Christensen, Hanne K; Collins, Ronan; Gommans, John; Kruuse, Christina; Ntaios, George; Ozturk, Serefnur; Phillips, Stephen; Pocock, Stuart; Szatmari, Szabolcs; et al.
Abstract : Introduction: Nitrate-induced headache is common and may signify responsive cerebral vasculature. We assessed the relationship between nitrate headache and outcome in patients with acute stroke. Materials and methods: Patients were those randomised to glyceryl trinitrate (GTN) versus no GTN in the efficacy of nitric oxide in stroke trial. Development of headache by end of treatment (day 7), and functional outcome (modified Rankin Scale, primary outcome) at day 90, were assessed. Analyses are adjusted for baseline prognostic factors and give OR and mean difference (MD) with 95% CI. Results: In 4011 patients, headache was more common in GTN than control (360, 18.0% vs 170, 8.5%; p<0.001). Nitrate-related headache was associated with: younger age, female sex, higher diastolic blood pressure, non-total anterior circulation syndrome, milder stroke and absence of dysphasia (p<0.05). Nitrate headache was not associated with improved functional outcome (OR 0.90, 95% CI 0.73 to 1.10, p=0.30) or death (day 90) (HR 0.64, 95% CI 0.40 to 1.02, p=0.062), but reduced death or deterioration (day 7) (OR 0.45, 95% CI 0.25 to 0.82), death in hospital (OR 0.44, 95% CI 0.22 to 0.88) and improved activities of daily living (Barthel index, MD 3.7, 95% CI 0.3 to 7.1) and cognition (telephone interview cognitive screen, MD 2.0, 95% CI 0.7 to 3.3) (day 90). Non-nitrate headache was not associated with death, disability or cognition. Discussion and conclusion: Development of a nitrate headache by day 7 after stroke may be associated with improved activities of daily living and cognitive impairment at day 90, which was not seen with non-nitrate headache.